University Physics / Extended Version with Modern Physics: 9th Edition - Freedman Roger A; Young Hugh D (Addison-Wesley Publishing Company, 1996)
This book has been carefully constructed to ensure your success in the course - if you read the book and make use of its features. Units and Physical Quantities and Vectors, Motion along a Straight Line, Motion in Two or Three Dimensions, Newton's Laws of Motion, Work with Kinetic Energy, Potential Energy and Energy Conservation, Rotation of Rigid Bodies, Dynamics of Rotational Motion, Equilibrium and Elasticity, Gravitation, Periodic Motion, Fluid Mechanics, Temperature and Heat, Thermal Properties of Matter, Mechanical Waves, Waves Interference and Normal Modes, Sound and Hearing, Gauss's Law, Electric Potential, Direct-Current Circuits, Sources of Magnetic Field, Electromagnetic Induction, Inductance, Alternating Current, Electromagnetic Waves, Geometric Optics, Optical Instruments, Interference, Diffraction, Relativity, Quantum Mechanics, Atomic Structure, Nuclear Physics, Appendices, Index.